Handbook of food-drug interactions - McCabe, Beverly J. (CRC Press LLC, 2011)
While pharmacists may know that a particular drug is inactive in a given pH environment, they may not know the pH of common foods. For dietitians the situation is reverse. With contributions from pharmacy, dietetics, and medicine, this book serves as a guide to the interdisciplinary prevention or correction of negative food-drug interactions. While other books simply list potential food-drug interactions, this book gives specific recommendations based on frequency and severity of reactions. It provides special dietary modifications necessary for prevention of adverse side effects. It also identifies new foods, supplements, and ethnic dishes that may contribute significantly to food-drug interactions.